Evaluation of the Quality of Education and Care Programs for Children under the Age of 3 in Greece - Sotiropoulou, Eleni; Venetas, Georgios Stroungis; Giannakou, Vasiliki; Kasapi, Chrysoula (Global Journal of Educational Studies, 2024)
In recent years, the quality of education and care programs for children under the age of 3 has become an important issue of concern to both researchers and the policy-making community. Many organizations such as the OECD and UNICEF highlight the undeniable right of all children to have access to high-quality education and the long-term benefits for their holistic development. The purpose of this study is to explore the views of 426 educators from Greece on the quality of education and care programs for children under the age of 3. To conduct the survey, a questionnaire with 4 rating scales and 33 items was constructed and then posted on the official page of the national association of educators in social networks. This method for collecting the sample was chosen by the researchers due to the Covid-19 limitations of nurseries at the time of the survey. The results of the survey showed that the quality of the programs was at a relatively moderate level. The highest scores were for the scales for interactions created within the nurseries and the educational activities, while the lowest scores were for 'standards' for services and space requirements and staff-related conditions. Finally, the researchers anticipate that the results of the survey will provide useful information for educators to reflect on and will also contribute to the scientific literature on the quality of programs for children of that age group.